Why Computing Students Should Contribute to Open Source Software Projects: Acquiring developer-prized practical skills, knowledge, and experiences. - Spinellis, Diomidis (Communications of the ACM, 2021)
The article calls for computer students' involvement with open source software projects rather than focusing solely on computer programming. The integration of contributing to open source software projects within software engineering courses using a flipped classroom approach is recommended and the author describes the advice given to student contributors.